2008
DOI: 10.1507/endocrj.k07e-124
|View full text |Cite
|
Sign up to set email alerts
|

Repetitive Postprandial Hypertriglyceridemia Induces Monocyte Adhesion to Aortic Endothelial Cells in Goto-Kakizaki Rats

Abstract: Abstract. To compare the effects of postprandial hypertriglyceridemia and postprandial hyperglycemia on monocyte adhesion to endothelial cells, we investigated the effects of twice-daily standard diet (5% fat) and high-fat diet (30% fat) for 3 weeks on monocyte adhesion to endothelial cells and the expression of adhesion molecules in the aortic artery in nonobese type 2 diabetic Goto-Kakizaki rats. Fasting glucose, insulin, non-esterified fatty acid (NEFA), HbA1c, and body weight were comparable between the tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Motojima el al. [25] reported that elevation of ICAM-1, but not VCAM-1 mRNA, was observed in monocyte adhesion in type 2 DM rats fed a high-fat diet. And they reported that the fluctuation in blood glucose enhanced monocyte adhesion to the endothelium in diabetes rats using the NEMOes.…”
Section: Discussionmentioning
confidence: 99%
“…Motojima el al. [25] reported that elevation of ICAM-1, but not VCAM-1 mRNA, was observed in monocyte adhesion in type 2 DM rats fed a high-fat diet. And they reported that the fluctuation in blood glucose enhanced monocyte adhesion to the endothelium in diabetes rats using the NEMOes.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, experiments in rat models have shown that postprandial hypertriglyceridemia is associated with overexpression of ICAM-1 and increased monocyte adhesion in the aortic arterial wall. 96 Recent data also demonstrate that postprandial hyperglycemia is involved in increased leucocyte activation in patients with type 2 diabetes and familial combined hyperlipidemia. 97 Concerning the coagulation system, there are data demonstrating that postprandial hyperglycemia constitutes a significant predictor of platelet activation, as this was shown by measurement of urinary 11-dehydro-thromboxane (TX)B(2), a marker of in vivo platelet activation, in subjects with type 2 early diabetes.…”
Section: Pathophysiology Of Postprandial Dysmetabolism Induced Cardiomentioning
confidence: 99%
“…This process results in TGRL remnant particle formation and lipolysis products such as phospholipids and fatty acids. Previous studies have shown that TGRL lipolysis products cause aortic endothelial injury, including inflammation, elevated expression of reactive oxygen species (ROS), and increased vascular permeability (22)(23)(24)(25)(26)(27)(28)(29). Additionally, activating transcription factor (ATF) 3 appears to play an important role as a master regulator of inflammation in the aortic endothelium in response to TGRL lipolysis products (22,30).…”
Section: Electron Paramagnetic Resonance Spin Trapping Of Superoxide mentioning
confidence: 99%